Author Without Consciousness: Legal Aspects of Artificial Intelligence Creativity - Jovanović, Nikola (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
This chapter examines the legal implications of artificial intelligence (AI) in copyright law, focusing on whether works created autonomously or with AI assistance can be protected. The introduction situates AI within the historical trajectory of tools designed to mimic or replace human functions, including creativity. As AI generates content comparable to human-authored works, legal doctrine faces new challenges. The chapter distinguishes between two key issues: (1) potential copyright infringement during AI model training, and (2) the legal status of AI-generated content – the focus here. The second section clarifies basic AI concepts, types, and the ambiguities surrounding its creative capacities. The third part revisits foundational copyright principles, especially the link between authorship and protection, questioning whether non-human-generated works meet legal standards. The final section analyzes case examples and concludes that fully AI-generated works cannot qualify for copyright protection, lacking the essential human creative element. The author rejects formalistic views, emphasizing the necessity of human authorship.